2015
DOI: 10.1136/bmjopen-2015-008712
|View full text |Cite
|
Sign up to set email alerts
|

Effect of obesity on functional outcomes at 6 months post-stroke among elderly Koreans: a prospective multicentre study

Abstract: ObjectivesWe examined whether obesity based on body mass index (BMI) was a predictor of functional independence measure (FIM) at 6 months after ischaemic stroke onset while adjusting for stroke risk factors and covariates and stratifying by age group.DesignThis is an interim report of the Korean Stroke Cohort for Functioning and Rehabilitation that was designed as a nested case study within a nationwide hospital-based cohort.SettingWe identified all patients who were admitted to nine representative hospitals i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1
4

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 24 publications
2
27
1
4
Order By: Relevance
“…Some of the results from this study are consistent with several other studies that included only ischemic stroke subjects whereas the majority of the studies that support the obesity paradox included different patient populations (i.e. , only hemorrhagic [ 20 ], only ischemic [ 8 , 9 , 11 14 , 16 , 50 , 51 ], stroke or TIA [ 7 , 17 ], or both ischemic and hemorrhagic strokes [ 10 , 15 , 18 , 19 ]). It is important to point out these differences in the study population because the pathogenesis of ischemic stroke is markedly different from that of hemorrhagic stroke, thus the effect of obesity on post-stroke outcomes may not be the same [ 52 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Some of the results from this study are consistent with several other studies that included only ischemic stroke subjects whereas the majority of the studies that support the obesity paradox included different patient populations (i.e. , only hemorrhagic [ 20 ], only ischemic [ 8 , 9 , 11 14 , 16 , 50 , 51 ], stroke or TIA [ 7 , 17 ], or both ischemic and hemorrhagic strokes [ 10 , 15 , 18 , 19 ]). It is important to point out these differences in the study population because the pathogenesis of ischemic stroke is markedly different from that of hemorrhagic stroke, thus the effect of obesity on post-stroke outcomes may not be the same [ 52 ].…”
Section: Discussionsupporting
confidence: 90%
“…Although obesity is a modifiable risk factor for ischemic stroke [ 27 , 28 ], the reported effects of obesity on post-stroke outcomes of functional disability and of all-cause mortality have been conflicting. Whereas studies of the general population have found that increasing body mass concurrently increases the risk of functional disability [ 29 ] and of all-cause mortality [ 30 , 31 ], a number of observational studies in a stroke population have reported that obesity is associated with a decreased risk of functional disability [ 7 9 ] and all-cause mortality [ 7 , 13 18 , 20 ]; this apparent discrepancy is referred to as the obesity paradox. As a result of these findings, the American Heart Association and American Stroke Association recommend all individuals who are diagnosed with an ischemic stroke be screened for obesity [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that obesity was a positive factor for language deficit improvement in univariate analysis. The obesity paradox in functional recovery of ischemic stroke patients has been mentioned in many studies, and most observational data indicate a survival benefit and better functional outcome in obese patients after stroke [22][23][24][25]. However, obesity was not a statistically significant factor in multivariate analysis for aphasia recovery in the current study.…”
Section: Wwwe-armorgcontrasting
confidence: 49%
“…Comorbidity was assessed using the combined condition-and age-related score in the Charlson comorbidity index [13]. Educational level was asked and patients chose an answer from following options; elementary school graduate or less, middle school graduate, high school graduate, and Bachelor's degree or higher [14]. Pre-stroke functional level was assessed using modified Rankin scale [15].…”
Section: Demographic and Clinical Characteristics Of The Patientsmentioning
confidence: 99%